1999
DOI: 10.1017/s0033291799008612
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to assaultive violence: further specification of the sex difference in post-traumatic stress disorder

Abstract: Future research should focus on sex differences in the response to assaultive violence, including potential explanations for females' greater probability to experience avoidance and numbing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
269
9
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(309 citation statements)
references
References 13 publications
21
269
9
9
Order By: Relevance
“…Previous research has consistently observed that women are approximately twice as likely as men to receive PTSD diagnoses even when the type of traumatic event is taken into account (Breslau, Chilcoat, Kessler, Peterson, & Lucia, 1999). What the present research suggests is that gender does not qualitatively change posttraumatic stress symptomatology.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous research has consistently observed that women are approximately twice as likely as men to receive PTSD diagnoses even when the type of traumatic event is taken into account (Breslau, Chilcoat, Kessler, Peterson, & Lucia, 1999). What the present research suggests is that gender does not qualitatively change posttraumatic stress symptomatology.…”
Section: Discussioncontrasting
confidence: 42%
“…Norris, 1992;Breslau et al 1997Breslau et al , 1999, even after controlling for type of trauma or 'most upsetting' trauma (e.g. Norris, 1992;Kessler et al 1995;Breslau et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, epidemiologic studies consistently demonstrate higher rates of full and partial PTSD in females than in males (Breslau et al 1991 Breslau et al 1997Davidson et al, 1991;Helzer et al, 1987;Kessler et al, 1995Kessler et al, 1999Norris, 1992;Stein et al, 1997) despite the fact that males are characterized by higher rates of trauma exposure. Thus, we included participants' gender in the analyses both as a unique predictor of PTSD as well as a control variable.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Posttraumatic Stress Disorder; PTSD; Cognitions; Anxiety; Trauma Exposure to traumatic events is quite common, with estimated lifetime rates ranging from 26% to 92.2% in men and from 17.7% to 87.1% in women (Breslau, Davis, Andreski, & Peterson, 1991;Breslau et al, 1999;Creamer, Burgess, & McFarlane, 2001;Kessler et al, 1995;Norris, 1992;Perkonigg, Kessler, Storz, & Wittchen, 2000;Resnick, Kilpatrick, Dansky, Saunders, & Best, 1993;Stein et al, 1997). Although many people experience trauma, only a subset of these individuals subsequently develops posttraumatic stress disorder (PTSD).…”
Section: Introductionmentioning
confidence: 99%